Toughness properties of steel-polypropylene fibre reinforced concrete under elevated temperature - Jameran, Aminuddin (2015)
Application of fibres in concrete which is also known as fibre reinforced concrete (FRC) has been found to improve the energy absorption or toughness of the material. However, only little information on FRC toughness is found when it is exposed to high temperature such as under prolonged heat or fire. The main objective of the study is to evaluate the toughness behaviour of FRC by experimentation when exposed to elevated temperature. The fibre used in the experimental work is steel (ST) or polypropylene (PP), and also the combination of both fibres. The fibre dosage varied between the ST and PP summarised as (100-0), (75-25), (50-50), (25-75) and (0-100). Meanwhile, the total volume fraction, Vf is fixed at 1.5% and they are exposed to elevated temperature at the following degree; room temperature (27 C), 200 C, and 400 C. The research shows that the addition of fibres in concrete enhanced the FRC toughness, however, it reduces as the exposure temperature increases.